Impact of facilitating continued accessibility to cancer care during COVID-19 lockdown on perceived wellbeing of cancer patients at a rural cancer center in Rwanda - Anne Niyigena; Vincent K. Cubaka; Pacifique Uwamahoro; Robert Gatsinzi Mutsinzi; Benigne Uwizeye; Blandine Mukamasabo; Cyprien Shyirambere; Bosco Jean Bigirimana; Joel Mubiligi; Dale A. Barnhart (Public Library of Science (PLoS), 2023)
During the COVID-19 pandemic in Rwanda, Partners In Health Inshuti Mu Buzima collaborated with the Butaro Cancer Center of Excellence (BCCOE) to mitigate disruptions to cancer care by providing patients with free transportation to treatment sites and medication delivery at patients' local health facilities. We assessed the relationship between facilitated access to care and self-reported wellbeing outcomes. This cross-sectional telephone survey included cancer patients enrolled at BCCOE in March 2020. We used linear regression to compare six dimensions of quality of life (EORTC QLQ-C30), depression (PHQ-9), anxiety (GAD-7), and financial toxicity (COST) among patients who did and did not receive facilitated access to care. We also assessed access to cancer care and whether patient wellbeing and its association with facilitated access to care differed by socioeconomic status. Of 214 respondents, 34.6% received facilitated access to care. Facilitated patients were more likely to have breast cancer and be on chemotherapy. Facilitation was significantly associated with more frequent in-person clinical encounters, improved perceived quality of cancer care, and reduced transportation-related barriers. Facilitated patients had significantly better global health status (β = 9.14, 95% CI: 2.3, 16.0, p <0.01) and less financial toxicity (β = 2.62, 95% CI: 0.2,5.0, p = 0.03). However, over half of patients reported missing or delaying appointment. Patient wellbeing was low overall and differed by patient socioeconomic status, with poor patients consistently showing worse outcomes. Socioeconomic status did not modify the association between facilitated access to care and wellbeing indicators. Further, facilitation did not lead to equitable wellbeing outcomes between richer and poorer patients. Facilitated access to care during COVID-19 pandemic was associated with some improvements in access to cancer care and patient wellbeing. However, cancer patients still experienced substantial disruptions to care and reported low overall levels of wellbeing, with socioeconomic disparities persisting despite facilitated access to care. Implementing more robust, equity-minded facilitation and better patient outreach programs during health emergencies may promote better care and strengthen patient care overall and effect better patients' outcomes.